Persepsi Pelajar terhadap Benteng Moraya Sebagai Atraksi Wisata Sejarah – Budaya di Tondano, Provinsi Sulawesi Utara - Jemmy Rudolf Pangemanan; Dianne O. Rondonuwu; Benny Irwan Towoliu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
In the current historical and cultural tourism, the district government has excavated various remnants of the Moraya fortress that has been buried for three centuries around the coast of Lake Tondano as a historical witness of the Tondano people's battle against the Dutch colonial. This very interesting tourist attraction is seen from the enthusiasm of local residents and local residents visiting the location. But the recognition of residents, especially school children, many are not satisfied after they visited the tour. The purpose of this research is to examine the Students' Perception of Tourism Objects of Fort Moraya Tondano, As Historical - Cultural Tourism. The analytical method used is qualitative and quantitative (mix method). The research instruments used were questionnaire, observation and documentation. Likert scale is used to categorize each question in the form of scoring to facilitate answers to respondents' ratings. The analysis used is descriptive using tables and percentages. The results of the 13 indicators that were asked there were seven indicators answered with positive agreement, and the rest were hesitant (neutral). Managers need to evaluate the historical-cultural tourist attraction of Fort Moraya.